Analysis of Non-Cash Payment System on Economic Growth and Financial System Stability in Indonesia - Apriyaningsih, Lilis; Rangkuty, Dewi Mahrani; Efendi, Bakhtiar; Sari, Wahyu Indah (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze the impact of non-cash payment systems on economic growth and financial system stability in Indonesia. The non-cash payment instruments examined include e-money, debit cards, credit cards, the Bank Indonesia National Clearing System (BINCS), and real-time gross settlement (RTGS). The method used is a simultaneous equation model with the two-stage least squares (TSLS) approach, utilizing time-series data from 2013 to 2023. The results show that e-money and BINCS have a positive influence on economic growth, while RTGS and interest rates have a significant negative effect. Meanwhile, debit cards and credit cards significantly affect interest rates, with debit cards having a positive effect and credit cards a negative one. Furthermore, economic growth significantly contributes to lowering interest rates. These findings highlight that non-cash payment systems can enhance transaction efficiency, accelerate money circulation, and support monetary policy through their influence on interest rates. Therefore, strengthening digital payment systems is essential for promoting sustainable economic growth and maintaining national financial system stability.